Economic Impact of E-Governance with Special Reference to Bihar: The Role of Governance in E-Governance Efficiency (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper looks at the governance of corporate networks and the effects of governance on the efficiency of networks. Three specific e-governance models, or shapes, are produced with an emphasis on their distinct structural characteristics. Propositions are formulated to analyze the criteria for each form's efficacy. Then it addresses the tensions implicit in each form, followed by the position that management should play in resolving these tensions.Finally, it examines the evolution of government. However, there is still a major gap between the acclamation and attention networks received and the information we have regarding the overall operation of networks, considering much improvement achieved by scholars researching networks of organizations across the past 15 years and more. We relate to the mechanism through which such network situations contribute to different network-level effects by network functioning. Knowing the workings of networks is critical because it is only then that we can properly explain why networks deliver such effects, regardless of whether networks are the products of bottom-up processes or are the outcome of strategic decisions taken by network members or government officials.